Bioinformatics Analysis of Potential Biomarkers for Lupus Nephritis - Zhao Liang; Suresh V Chinni; Zhiming Tang (Malaysian Journal of Science (MJS), 2025)
Lupus Nephritis (LN) is a complication of Systemic Lupus Erythematosus affecting the kidney. The purpose of this study was to identify signalling pathways and hub genes involved in the pathogenesis of LN. Methods: The mRNA expression profiles of LN were obtained from the Gene Expression Omnibus database, and differentially expressed genes (DEGs) were identified using the online tool GEO2R. Enrichment analysis was conducted in DAVID. The Protein-Protein Interaction network of DEGs was constructed in STRING, and hub genes were identified with Cytoscape. The hub genes were validated using differentially expressed proteins (DEPs) from proteomics data to identify potential biomarkers for LN. Results: A total of 138 DEGs were identified, primarily associated with immune response, neutrophil chemotaxis, and antimicrobial humoral immunity. In KEGG analysis, the NOD-like receptor signalling pathway and the Cytokine-cytokine receptor interaction pathway were mainly involved. Nine hub genes of LN, including Ifit1, Ifit3, Ifih1, Ifi44, Irf7, Irf9, Oasl1, Stat1, and Usp18 were identified. Conclusion: Ifi44 and Stat1 were expressed in both DEGs and DEPs. Ifi44 and Stat1 may be potential biomarkers and therapeutic targets for LN.